Effective exchange rates, current accounts and global imbalances - Joscha Beckmann; Robert Czudaj (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This study analyzes the dynamics between real e ective exchange rates and current account patterns from a novel perspective. We start by dissecting long-run and time-varying short-run dynamics between both variables. Following this, we extend our framework by including interest rates into our analysis. Finally, we examine common exchange rate and current account dynamics based on common factors derived from a principal components analysis. Our results show that a real appreciation is positively related to a worsening of the current account in most cases. The adjustment pattern is time-varying but suggests that the causality mainly runs from e ective exchange rates to current accounts and occurs through valuation e ects. However, an extension of our framework based on monthly data shows that trade balance adjustment is observed less frequently. From a global point of view, cross-country trends which drive exchange rates and current accounts also share similar dynamics over the long-run.
Keywords: F31; F32; G15; 330